2008
DOI: 10.1111/j.1464-5491.2008.02602.x
|View full text |Cite
|
Sign up to set email alerts
|

The NCEP‐ATPIII but not the IDF criteria for the metabolic syndrome identify Type 2 diabetic patients at increased risk of chronic kidney disease

Abstract: In Type 2 diabetes, NCEP-ATPIII, but not the IDF definition of MetS, identifies a subgroup of patients who have a higher risk of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…However, the association of IDF-defined MS with ischemic stroke was not significant. Luk et al 30 reported that in patients with type 2 DM, the ATP III but not the IDF definition of MS, defined a subgroup of patients who had a higher risk of chronic kidney disease. In the Japan Diabetes Complication Study, which enrolled 1424 type 2 DM patients who were followed for 8 years for evidence of CAD and stroke, the IDF definition showed no improvement in the prediction of adverse CVD events in comparison with the ATP III and WHO definitions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of IDF-defined MS with ischemic stroke was not significant. Luk et al 30 reported that in patients with type 2 DM, the ATP III but not the IDF definition of MS, defined a subgroup of patients who had a higher risk of chronic kidney disease. In the Japan Diabetes Complication Study, which enrolled 1424 type 2 DM patients who were followed for 8 years for evidence of CAD and stroke, the IDF definition showed no improvement in the prediction of adverse CVD events in comparison with the ATP III and WHO definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the proportion of non-obese individuals among those with MS diagnosed according to the NCEP criteria is 9.7-18.9% in Europeans (23, 34), 7.6-35.6% in Asians except for Japanese (8,10,24,35,36), 25.4-33.6% in Japanese (20,22) and 31.3-32.6% in Asians with type 2 diabetes (6,25). The median of these values is higher among Asians than Europeans (32.5% vs. 14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with ESRD has been increasing worldwide, with diabetic nephropathy recognized as the most significant cause of this increase (3), and hypertension, dyslipidemia and obesity are considered to independently damage the kidneys (4,5). A number of studies have recently focused on the relationship between metabolic syndrome (MS), the clustering of metabolic risk factors within the same individual and CKD (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…MS was diagnosed in older women who had three or more of the following criteria: abdominal obesity (UAC > 88 cm), TG values X ≥ 150 mg.dl-1, HDL-C values X <50 mg.dl -1 ; BP values ≥ 130/85 mmHg, or taking antihypertensive treatment, and plasma fasting glucose levels 110 ≥ mg.d l-1 (Luk et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic syndrome (MS) is a health complication that has been strongly associated whit the elder population (Bener et al, 2010), which is a disease of complex nature, consisting of five major clinical components: abdominal obesity, atherogenic dyslipidemia, elevated blood pressure and insulin resistance without glucose intolerance in potentially harmful combinations that significantly rise cardiovascular risk (Luk et al, 2008), various authors report straight associations of the MS with an endomorphic somatotype (Gordon et al, 1987;Koleva et al, 2002;Herrera et al, 2004;Kalichman et al, 2004;Buffa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%